Awareness of Turkish Pre-Service Teachers about the Risks of Electromagnetic Radiation in Daily Life Cases - Handan Ürek (Universitas Pendidikan Indonesia, 2021)
This study aimed to investigate Turkish pre-service teachers' awareness about electromagnetic radiation risks, which stem from diagnostic imaging at the hospitals and cell phone use in daily life. The study was based on survey research. A total of 138 education faculty students from the fields of Science Teaching [ST], Classroom Teaching [CT], and English Language Teaching [ELT] participated in the study. Data were collected with the help of a questionnaire involving five cases. Both qualitative and quantitative approaches were utilized in data analysis. The results showed that most of the participants agreed on the hazardousness of the cases. However, their risk awareness varied from case to case. Most ST and CT students were determined to possess acceptable responses in addition to partially acceptable responses. On the other hand, ELT students were determined to favor unacceptable responses. Besides, the participants held several misconceptions. To conclude, the participants' awareness levels were found to be significantly related to their educational field for all cases except the first case. Addressing such popular subjects in the elective courses for all undergraduate students during university education is expected to provide beneficial results.